Elaborating Appropriate Models of the Sustainable Financing Instrument in Public Private Partnerships (PPP) In Infrastructure Projects - Prawitra Thalib; Faizal Kurniawan; Erni Agustin; Rizky Amalia (IPTEK Journal of Proceedings Series, 2017)
One alternative to accelerate infrastructure development in Indonesia is by involving the private sectors in the financing and development. In principle, Public Private Partnerships (PPP) can be classified into two, namely: a partnership project which idea came from the initiation of the government (solicited) and partnership project which idea came from the initiation of the business entities (unsolicited). To facilitate the implementation of the Public Private Partnership (PPP), the financing instruments that exist currently may be used to support the implementation of the Public Private Partnership (PPP). The importance of involving a third party other than investor and the government is related to the fulfillment of capital requirements and risks sharing in the event of loss. Although the rules clearly have been enacted, the infrastructure projects in Public Private Partnership (PPP) seem less attractive to investors. One of the causes is that the capital required by investors is too great with very high risk when investment in infrastructure is slow yielding. It is important to propose the scheme of sustainable financing which may allocate the PPPs’ risks proportionally.Until now, the government is too fixated with large cooperation projects with the private sectors, while the scheme offered is a Build-Operation-Transfer (BOT) scheme. This scheme is sometimes burden the investors, because the greatest risk is in the hands of investors. Regarding the financing of the Public Private Partnership (PPP), conventional financing such as a bank guarantee or sharia financing (‘kafalah’) can be carried out. Two such financing can be used in the Public Private Partnership (PPP), so it will increase the interest of investors to build infrastructure using Public Private Partnership (PPP). It is because such financing can overcome the difficulties of gaining large capital and also reduce the burden of risk borne by investors.